Diseño Conceptual de un Cohete de Tres Etapas Para Transportar Una Carga Útil De 200 kg A Una Órbita Baja - Ospina Contreras, Daimer; Roldán Torres, Luis Carlos (TECCIENCIA, 2020)
This article presents the conceptual design of a three-stage rocket to carry 200 kg payload to low Earth orbits (by the acronym LEO). From a case study of the ﬂight path of a three-stage rocket with solid propel- lants, proceed to select the propellant mixture that meets the design require- ments and path raised ﬂight, taking into account that it can produce nation- wide. The propellant thermochemical behavior is obtained with CPROPEP software. Knowing the values of pressure, temperature and speciﬁc heat ra- tio in the combustion chamber proceeds to design rocket engines to ensure total velocity change in the system equivalent to those obtained in the anal- ysis of the ﬂight path. With the design of the propulsion duct materials that withstand the thermal loads and pressure, to give way to structural design giving an approximation of carrier rocket are chosen.